MODEL INQUIRY BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA BANGUN RUANG DI SEKOLAH DASAR - Khusna, Fatma Nadiatul; Mardati, Asih; Johari, Yudy (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
Mastery of mathematics learning requires the ability to understand concepts to be able to achieve maximum mathematics learning achievement. This is proven through pretest questions with results that are still far from complete. The aim of classroom action research is to increase the understanding of mathematical concepts of fifth grade students at Muhammadiyah Nitikan Elementary School in spatial construction material using the inquiry based learning model. The subjects of this research were 30 students in class V of SD Muhammadiyah Nitikan for the 2023-2024 academic year, consisting of 17 male students and 13 female students. The data collection techniques used were tests, observation, interviews and documentation. The results of this research show that the inquiry based learning model is successful in increasing students' understanding of mathematical concepts in spatial construction material. The learning outcomes during the pre-cycle, the average score obtained was 38 with an average percentage of completeness of 3% and an average percentage of incompleteness of 97%. After the first cycle of action, the results showed an average of 73 with an average percentage of completeness of 70% and the average percentage of not 30% complete, while in Action Cycle II the test results reached an average score of 91 with an average percentage of completeness of 83% and an average percentage of incompleteness of 17%.